If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = -53 Reorder the terms: 5 + 3x = -53 Solving 5 + 3x = -53 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = -53 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = -53 + -5 3x = -53 + -5 Combine like terms: -53 + -5 = -58 3x = -58 Divide each side by '3'. x = -19.33333333 Simplifying x = -19.33333333
| 2v-5=4v+12 | | 8m+2n-7m+4n= | | 2j+10=-8j | | 4/3p=5/4p-1/2 | | 29*p=20 | | 18/11=3/x | | 4x-39=33-2x | | 4(x-3/7) | | 0.4y=-1.8 | | 21+27x=28+20x | | 8a+1=121 | | F=5/4(n-33) | | -10-2v-6v=-3v+5v | | -9-9u=-13-9u-4 | | 7-2(2+4)= | | 9x+60=-3 | | y=x^0 | | -72+7x=53+2x | | r^2=4/9 | | 9x-6y=-3 | | X/96=7/28 | | 8.2=x-1 | | 4/8•0.5 | | 44x+5=49 | | -4x-16=6-6x | | x=331+0.6(10) | | 3m+13m-14=-14+16 | | (2/1)-8 | | (4x-6)+(5x+10)= | | 2(4x)+5=60+25 | | 28-5(3)=c | | 36=24-7x+5x |